2008
DOI: 10.1177/0891988708324940
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Alzheimer Disease Assessment Scale-cognitive Part in Predicting Progress for Amnestic Mild Cognitive Impairment to Alzheimer Disease

Abstract: The aim of this study was to verify the usefulness of Alzheimer Disease Assessment Scale-cognitive subscale (ADAS-Cog), in screening participants at risk of developing Alzheimer disease (AD) among populations with amnestic mild cognitive impairment(aMCI). 98 outpatients with aMCI were recruited. Participants were revaluated after 1 year: 44 (44.9%) were progressed to AD (progressors), while 54 (55.1%) did not convert (nonprogressors MCI). At baseline, cognitive performances were more impaired in progressors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
(44 reference statements)
4
22
0
1
Order By: Relevance
“…In the regression analysis, ADAS-Cog had a greater odds ratio to predict dementia than apathy itself; this confirmed previous findings that underlined the importance of this brief assessment scale in the prediction of dementia in amnestic MCI after a 1-year follow-up [48] . In the present study, this finding became even stronger as a longer period of follow-up and a larger number of sample patients have been considered.…”
Section: Discussionsupporting
confidence: 77%
“…In the regression analysis, ADAS-Cog had a greater odds ratio to predict dementia than apathy itself; this confirmed previous findings that underlined the importance of this brief assessment scale in the prediction of dementia in amnestic MCI after a 1-year follow-up [48] . In the present study, this finding became even stronger as a longer period of follow-up and a larger number of sample patients have been considered.…”
Section: Discussionsupporting
confidence: 77%
“…The TDAS is a modifi cation of the Alzheimer's Disease Assessment Scale 14 and its subscale, the Alzheimer's Disease Assessment Scale-Cognitive subscale, 15 which is widely used to measure decline in cognitive function. The TDAS also runs on the Microsoft Windows Operation system and touch-panel-type desktop PC and shows a high correlation with the Alzheimer's Disease Assessment Scale-Cognitive subscale ( r = 0.69; P < .001).…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…However, some studies have suggested that at baseline other cognitive domains, including executive function and lower cognitive abilities, better predict conversion from MCI to AD (e.g. Rozzini et al, 2008). Still other studies suggest that non-amnestic or multi-domain MCI patients convert to AD at lower rates than amnestic MCI patients (Maioli et al, 2007).…”
mentioning
confidence: 99%